Challenges of Slum Upgrading in Port Harcourt, River State, Nigeria - Adewale O Yoade; Sesan A Adeyemi (The Indonesian Journal of Planning and Development, 2020)
Environmental decay in a city is essentially caused by rapid urbanization and the mismatch in the provision and maintenance of housing and infrastructure. This study examined challenges of slum upgrading in Port Harcourt, Nigeria. The study aims to examine slum areas and their living conditions, and finding out the most critical and problematic zone of the slums Two sources (primary and secondary) of data were utilized in the study: The study population for this study was the residents of Diobu and Waterside in Port Harcourt, River State. Both descriptive and inferential statistics were used to analyse the data appropriately. Findings established that 11.3% acquired primary education, 29.0% have secondary education, and 14.0% had NCE, 21.0% had both HND and degree and 3.8% had no formal education. Findings showed that 31.7% of the residents were owners of the building while 68.2% were living in rented apartments. Findings revealed that 40.9% of the respondents have bad drainage system which would lead to dirty environment and 6.5% having very good drainage system. The study concluded that majority of building structures in the study area are old that existed for decades without maintenance and the surrounding environment very poor due to neglect.